Comparison of Haemodynamic Stability of Etomidate versus Propofol for Induction of Anaesthesia in Patients undergoing Coronary Artery Bypass Graft Surgery - Hossain, Mir Mahmud; Alam, Mahbub ul; Akter, Suraya; Hussain, Md Pervez Altaf (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Maintenance of hemodynamic stability during induction and obtundation of intubationstress response are the prime consideration of general anaesthesia. Aims: The purpose of the study is to compare the hemodynamic effects of etomidate and propofol duringinduction and intubation in patients undergoing Coronary Artery Bypass Graft Surgery(CABG). Materials and Methods: This prospective, double-blind randomized clinical trial, total eighty patientswere randomly allocated and divided into two groups based on the induction agent used for anaesthesia(etomidate group or E group) and (propofol group or P group). Heart rate(HR), Mean Arteriolar Bloodpressure(MAP), Cardiac Output (CO) & Cardiac Index(CI) were recorded at preoperative Baseline(T1), atpremedication(T2), at induction(T3), at intubation (T4), 1 min after induction(T5), 3 min after induction(T6),5 min after induction(T7). The use of vasopressors was also recorded, required for both the groups. Results: Before induction, there was no significant difference in hemodynamics between the groups (p>.05). At induction, intubation & up to 5 min after induction thereafter all the hemodynamic parameterswere significantly different from baseline value in both groups (p < .001). During the comparison betweentwo group, it was noted that, in P group, propofol caused pronounced reduction of HR, MAP, CO & CI incomparison to E group, at induction(T3), at intubation (T4), 1 min after induction(T5), 3 min afterinduction(T6). The use of vasopressors was also in higher incidences in P group than E group. Conclusion: This study confirms that Etomidate provides a stable hemodynamic condition in contextwith propofol during induction, intubation & immediate post induction period and this hemodynamicstability can improve the clinical outcomes in patients undergoing CABG. JBSA 2021; 34(1): 43-49